A theoretical model to access the feasibility of low-cost airlines. - Ho, Eunice Wai Yee. (2008)
The objective of the dissertation is to develop a theoretical model to assess the feasibility of low-cost low-fare no-frills airlines. The study carried out included an analysis of the deregulation of the airline industry in the U.S. and Europe and the growth of low-cost low-fare no-frills airlines.